OPTIMALISASI PELAYANAN HAJI KEMENTRIAN AGAMA KABUPATEN 50 KOTA PERSPEKTIF MANAJEMEN SYARIAH - Wiko Yandra; Zuwardi (CV. Adiba Aisha Amira, 2025)
The purpose of organizing the Hajj pilgrimage carried out by the government is to provide maximum safety, advice, and service to Hajj pilgrims so that they can complete their journey in accordance with Islamic beliefs. The government has a duty to provide protection, assistance, and advice. through offering security, medical care, transportation, administrative support, and other needs during the entire Hajj pilgrimage, especially for senior pilgrims. The Ministry of Religion is tasked with preparing, planning, and providing the infrastructure and facilities needed to carry out the Hajj pilgrimage. The purpose of this study is to evaluate how well the Ministry of Religion of Limapuluh Kota Regency serves Hajj pilgrims. Qualitative research is the methodology used in this study. The data sources used are primary data from interviews with employees of the Ministry of Religion of Limapuluh Kota Regency and secondary data from documents accessed during the interview. In this study, documentation, interviews, and observations are the methods used to collect data. In addition, the Miles and Huberman data analysis model—which consists of data reduction, data presentation, and conclusions/verification—is the data analysis technique used. Based on the research findings, the Ministry of Religious Affairs of 50 Cities Regency optimizes services by implementing management functions, such as organizing, planning, enforcing, and controlling, in addition to providing oral services to elderly pilgrims. This is done in writing and in action to facilitate the understanding of older members of the congregation regarding the instructions.